RIG-I and MDA5 Protect Mice From Pichinde Virus Infection by Controlling Viral Replication and Regulating Immune Responses to the Infection - Brisse, Morgan; Huang, Qinfeng; Rahman, Mizanur; Di, Da; Liang, Yuying; Ly, Hinh (Frontiers in Immunology, 2021)
RIG-I and MDA5 are major cytoplasmic innate-immune sensor proteins that recognize aberrant double-stranded RNAs generated during virus infection to activate type 1 interferon (IFN-I) and IFN-stimulated gene (ISG) expressions to control virus infection. The roles of RIG-I and MDA5 in controlling replication of Pichinde virus (PICV), a mammarenavirus, in mice have not been examined. Here, we showed that MDA5 single knockout (SKO) and RIG-I/MDA5 double knockout (DKO) mice are highly susceptible to PICV infection as evidenced by their significant reduction in body weights during the course of the infection, validating the important roles of these innate-immune sensor proteins in controlling PICV infection. Compared to the wildtype mice, SKO and DKO mice infected with PICV had significantly higher virus titers and lower IFN-I expressions early in the infection but appeared to exhibit a late and heightened level of adaptive immune responses to clear the infection. When a recombinant rPICV mutant virus (rPICV-NPmut) that lacks the ability to suppress IFN-I was used to infect mice, as expected, there were heightened levels of IFN-I and ISG expressions in the wild-type mice, whereas infected SKO and DKO mice showed delayed mouse growth kinetics and relatively low, delayed, and transient levels of innate and adaptive immune responses to this viral infection. Taken together, our data suggest that PICV infection triggers activation of immune sensors that include but might not be necessarily limited to RIG-I and MDA5 to stimulate effective innate and adaptive immune responses to control virus infection in mice.